Analysis of the Antioxidant & Antimutagenic Potential of CGA, a phenolic component of Coffee, in Inhibiting Mutations in Salmonella typhimurium - Niaman, Ambreen; Treml, Jack; Logan, Randall (Midwestern Journal of Undergraduate Sciences, 2024)
Excess cellular radical oxygen species are associated with an increase in cellular, including genetic damage. In somatic cells, this may lead to cancer when genes associated with cell growth and reproduction are impacted. Opposing radical oxygen species are antioxidants which can quench free radicals that otherwise may damage a cell’s DNA. The body produces some antioxidants naturally, such as glutathione, while others are obtained through diet, including vitamins C and E. Chlorogenic Acid (CGA) is one example of a polyphenolic compound in coffee with the potential to exhibit antioxidant and antimutagenic properties. The concentration of CGA in a commercially available coffee was measured and its potential to exhibit antioxidant properties was assessed. An extract was prepared in which the spectral properties of CGA were exploited to quantitate its concentration in green coffee extract via HPLC. The antioxidant activity of CGA was characterized by measuring its relative ability to neutralize free radicals using a colorimetric assay vs. a pure vitamin C standard. The antimutagenic activity of CGA was to be assessed via an Ames test using mutant Salmonella strains incapable of producing the amino acid histidine. The results demonstrated a considerable amount of CGA in green coffee extract, that exhibited antioxidant properties. Future work will assess antimutagenic effects of CGA in the extract compared to the antimutagenic effect of vitamin C and pure CGA standards. Overall, these results suggested that coffee beverages may serve as potent antioxidants with the potential to protect consumers from the harmful effects of mutagenic free radicals.